2021
DOI: 10.3390/atmos12080932
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Tropical Cyclone Idai Simulations to Cumulus Parametrization Schemes

Abstract: Weather simulations are sensitive to subgrid processes that are parameterized in numerical weather prediction (NWP) models. In this study, we investigated the response of tropical cyclone Idai simulations to different cumulus parameterization schemes using the Weather Research and Forecasting (WRF) model with a 6 km grid length. Seventy-two-hour (00 UTC 13 March to 00 UTC 16 March) simulations were conducted with the New Tiedtke (Tiedtke), New Simplified Arakawa–Schubert (NewSAS), Multi-Scale Kain–Fritsch (MSK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 58 publications
0
0
0
Order By: Relevance
“…In the field of tropical cyclone simulation, researchers have studied the influences of different parameterization schemes on typhoon tracks and intensity. These studies found that the choice of different parameterization schemes may lead to different simulation results, and these differences may involve simulated typhoon tracks, intensity, structure, and precipitation [12][13][14][15][16][17][18][19]. The study of different parameterization schemes will provide a deeper understanding of the dynamic mechanisms driving typhoon behavior and development.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of tropical cyclone simulation, researchers have studied the influences of different parameterization schemes on typhoon tracks and intensity. These studies found that the choice of different parameterization schemes may lead to different simulation results, and these differences may involve simulated typhoon tracks, intensity, structure, and precipitation [12][13][14][15][16][17][18][19]. The study of different parameterization schemes will provide a deeper understanding of the dynamic mechanisms driving typhoon behavior and development.…”
Section: Introductionmentioning
confidence: 99%